Total Synthesis of Deoxypyridinoline and Deoxypyridinoline-13C2,15N1 - Ishii, Hiroaki; Tanaka, Nao; Shigeta, Ryosuke; Kondo, Saki; Usuki, Toyonobu (Synthesis, 2025)
Collagen fibers, which make up 30% of all proteins in vertebrates, are extracellular matrix proteins that provide mechanical strength to connective tissues such as skin and bone, forming the structural foundation of the body. Deoxypyridinoline, a collagen cross-linking amino acid first isolated from bovine bone in 1982, is released into the bloodstream during bone metabolism alongside degraded bone tissue. This makes it a promising biomarker for quantitatively assessing diseases associated with abnormal bone resorption. In this study, we achieved the total synthesis of deoxypyridinoline from commercially available amino acids in five steps with an overall yield of 20%. This synthetic method provides a scalable alternative to isolating the compound from natural sources. As part of ongoing research into its use as a biomarker, we also synthesized isotopically labeled deoxypyridinoline-13C2,15N1, which can be used as an internal standard for quantitative analysis.
Keywords: synthesis; amino acids; deoxypyridinoline; bone; collagen; isotopic labeling